WJ9708012 exerts anticancer activity through PKC-α related crosstalk of mitochondrial and endoplasmic reticulum stresses in human hormone-refractory prostate cancer cells - Kuo Ting-chun; Huang Wei-jan; Guh Jih-hwa (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the anticancer mechanism of a methoxyflavanone derivative, WJ9708012, highlighting its role on a crosstalk between endoplasmic reticulum (ER) and mitochondrial stress. Methods: Cell proliferation was examined using sulforhodamine B assay. Cell-cycle progression, Ca2+ mobilization and mitochondrial membrane potential (ΔΨm) were detected using flow cytometric analysis. Protein expression was detected using Western blot. Results: WJ9708012 displayed an antiproliferative and apoptotic activity in human hormone-refractory prostate cancer cells with IC50 values of 6.4 and 5.3 μmol/L in PC-3 and DU-145 cells. WJ9708012 induced a prompt increase of cytosolic Ca2+ level and activation of protein kinase C (PKC)-α. The cleavage of μ-calpain was also induced by WJ9708012. Furthermore, WJ9708012 induced cell-cycle arrest at G1-phase associated with down-regulation of cyclin D1, cyclin E and cyclin-dependent kinase-4 expressions. It also caused a rapid and time-dependent decrease of phosphorylation level of mTOR (Ser2448), 4E-BP1 (Thr37/Thr46/Thr70) and p70S6K (Thr389), indicating the inhibition of mTOR-mediated translational pathways. The ER stress was activated by the identification of up-regulated GADD153 and glucose-regulated protein-78 protein levels. The subsequent mitochondrial stress was also identified by the observation of a decreased Bcl-2 and Bcl-xL expressions, an increased truncated Bid and Bad and a loss of ΔΨm. Conclusion: WJ9708012 induces an increase of cytosolic Ca2+ concentration and activation of PKC-α. Subsequently, a crosstalk between ER stress and mitochondrial insult is induced, leading to the inhibition of mTOR pathways and arrest of the cell-cycle at G1 phase. The apoptosis is ultimately induced by a severe damage of mitochondrial function.